The determinants of stock market volatility: Macroeconomic fundamentals and investor sentiment / Nathrah Ya’cob @ Mohd Yacob - Nathrah, Mohd Yacob (2016)
Stock market volatility is an important risk indicator of stock returns. Investors are hesitant to invest in high stock market volatility, thereby affecting the market. This warrants the need to identify possible determinants of stock market volatility. This study focuses on volatility in the Malaysian stock market. Lack of information about the causes of volatility results in inaccurate investment strategies, also affecting the ability of regulators to take measures to eradicate potential bubbles caused by irrational exuberance. The present study examines the ability of macroeconomic fundamentals and investor sentiment in predicting the volatility of the stock market. Specifically, the objectives of this thesis are: (i) to examine the predictive value of macroeconomic fundamentals on the volatility of the Malaysian stock market; (ii) to investigate the predictive value of investor sentiment on the volatility of the Malaysian stock market; and, (iii) to determine whether macroeconomic fundamentals and global financial crisis affect the predictability of investor sentiment on the volatility of the Malaysian stock market. The third research objective serves as a robustness test in determining the validity of the newly-constructed Investor Sentiment Composite Index. The period of investigation spans from 2000 to 2012, highlighting the duration of the global financial crisis. Predictability of macroeconomic fundamentals and investor sentiment with respect to volatility of the stock market was modelled with auto-regressive distributive lags (ARDL) (p, q). Only inflation rate and money supply displayed short-run dynamics with the volatility of the Kuala Lumpur Composite Index (KLCI) during the period of study. This contradicts previous empirical research. Additionally, the newly-constructed Investor Sentiment Composite Index showed significant predictive power for the iv volatility of the KLCI. Investor sentiment predicted the volatility of the KLCI as early as four months in advance during the period of crisis and three months prior to event during the whole period of study. Investor sentiment retained its predictive value even after being controlled for the 2008 global financial crisis and macroeconomic fundamentals. Interestingly, it is found that investor sentiment significantly predicted the volatility of the Malaysian stock market during the global financial crisis, while macroeconomic fundamentals displayed no significant predictive value. This suggests that during crisis, extreme volatility is influenced more by non-fundamental factors, such as the irrational behaviour of investor sentiment. This provides a clearer picture to policymakers, regulators, and stock market participants in forecasting volatility, assisting in portfolio rebalancing, as well as in deciding on possible measures to avoid negative impact of excess volatility.